Взаимодействие ЕС и НАТО в решении проблемы миграционного кризиса - Kozubenko I. I. (Инновационные технологии в науке и образовании, 2016)
The article analyzes the process of EU and NATO co-ordination in the field of European security in the second half of 2015 - beginning of 2016, caused by the problem of illegal migration to Europe from Asia and the Middle East. Non-European nature of the crisis makes it impossible to solve it only in the framework of the EU and NATO.
Keywords: НАТО; нелегальная миграция; охрана границ; NATO; illegal immigration; border security